POSTMODERN ORGANIZATION AND NEW FORMS OF ORGANIZATIONAL CONTROL - Lončar, Dragan (Economic Annals, 2005)
This article displays postbureaucratic organisational concept as an adequate representative of all emerging organisational forms which are natural result of persistant initiatives to flexibilise and intensify workitig process. Under this term we assume all budding ‘sub-representatives * such as Total Quality Management (TQM), Just-in-time concept (JIT), network systems and joint ventures, virtual organisations, teamwork and other related structures. The author concludes that main virtues of new organisational paradigm are flexibility, decentralisation, higher employee empowerment, knowledge and information sharing, responsibility for the system as a whole and permanent learning. On the other hand, some downsides become obvious. Those are danger from anarchy, responsibility and stress, greater employees’ insecurity and resistancy to new practices. Furthermores, the paper shed light on power and identity dynamics through the lens of improved and still intentional methods of organisational control. The main argument is that compulsive desire to control never fades away, only the methods of control takes different, more advanced forms through organisational culture, vocabulary and discourses, monitoring at a distance, peer evaluation inside teams, employee selection and many others.